La recreación como elemento potenciador de las habilidades y destrezas en los estudiantes de 13 a 15 años con síndrome de Down en el instituto de Educación Especial El Oro 2012-2013 - Ávila Ríos, Carlos Humberto (2013)
To try to solve the problem, an alternative proposal has been proposed, which consists of the elaboration of a manual of recreational activities for students with Down Syndrome of the Special Education Institute of El Oro.